Enhancement gain of broadband elliptical microstrip patch array antenna with mutual coupling for wireless communication - Ali Khalid Jassim; Raad H. Thaher (Institute of Advanced Engineering and Science, 2019)
The paper is presented analysis, design and manufacturing single optimize parameters of a new broadband elliptical patch antenna with microstrip center feed line and the array has been implemented to improve gain antenna. The antenna array dimension of mm3 and fabricated on an FR-4 epoxy substrate having relative dielectric constant =4.3, loss tangent tan (δ) =0.002 and the feed line used has characteristic impedance of 50Ω and added the triangle notch structure .Thus notch can achieve maximal additional enhancement impedance bandwidth are (3.679- 6.578) GHz, (13.84-25.142) GHz, (29.807-37.618) GHz and the gain 8dBi. The antenna array performance was modified by inserting stubs transition in feeding Microstrip line to reducing mutual coupling achieve impedance bandwidth (when S11-10dB). The modified antenna was designed to be used for wireless communication application. The simulation results are obtained using CST software.